2005
DOI: 10.1021/jm050257d
|View full text |Cite
|
Sign up to set email alerts
|

Specific Targeting Highly Conserved Residues in the HIV-1 Reverse Transcriptase Primer Grip Region. Design, Synthesis, and Biological Evaluation of Novel, Potent, and Broad Spectrum NNRTIs with Antiviral Activity

Abstract: Pyrrolobenzoxazepinones (PBOs) represent a new class of human immunodeficiency virus type 1 (HIV-1) nonnucleoside reverse transcriptase (RT) inhibitors (NNRTIs) whose prototype is 5. Molecular modeling studies based on the X-ray structures of HIV-1 RT prompted the synthesis of novel analogues which were tested as anti-HIV agents. The PBO derivatives specifically designed to target the highly conserved amino acid residues within the 12-13 hairpin, namely primer grip, proved to be very potent against the most co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 34 publications
0
27
0
Order By: Relevance
“…This residue not only is part of the NNRTI binding pocket but also belongs to the "primer grip" of HIV RT, and any mutation at this position has been shown to severely compromise the RNA-and DNA-dependent DNA polymerase activities of the enzyme (33). Indeed, this immutable residue has become the focus of the development of novel NNRTIs (17). In addition, upon the binding of many NNRTIs, the side chain of Tyr181, contained within the ␤4-␤7-␤8 sheet, have been reported to flip conformation from a "down" to an "up" position (38).…”
Section: Discussionmentioning
confidence: 99%
“…This residue not only is part of the NNRTI binding pocket but also belongs to the "primer grip" of HIV RT, and any mutation at this position has been shown to severely compromise the RNA-and DNA-dependent DNA polymerase activities of the enzyme (33). Indeed, this immutable residue has become the focus of the development of novel NNRTIs (17). In addition, upon the binding of many NNRTIs, the side chain of Tyr181, contained within the ␤4-␤7-␤8 sheet, have been reported to flip conformation from a "down" to an "up" position (38).…”
Section: Discussionmentioning
confidence: 99%
“…It is interesting that TMC125, a second generation NNRTI, efficiently inhibits HIV replication in M/M, even if at a concentration similar to those observed in CD4ϩ T lymphocytes [64]. In particular, it has been shown that the EC 50 of TMC125 against the laboratory strain HIV Bal is in the lower nanomolar range [2.0 (0.8 -4.0)] nm and highly similar to that observed for efavirenz {2.0 (0.9 -3.0) nm [64]}. The HIV Bal replication in M/M is also inhibited efficiently by the pyrrolobenzoxazepinones, a new class of NNRTIs designed to target the highly conserved primer grip within the ␣12-␣13 hairpin.…”
Section: Nnrtismentioning
confidence: 97%
“…Indeed, once the proviral DNA is integrated into the host genome, the production of viral particles is independent of the RT enzyme and thus, is not affected by the RTIs. For these reasons, the activity of several drugs acting at a late stage of HIV replication (anti-rev, anti-tat, transcription inhibitors, IFN-␣, IFN-␥, ampligen) has been tested in chronically infected M/M [64]. However, results were not encouraging, as all these drugs failed to suppress HIV replication.…”
Section: Protease Inhibitorsmentioning
confidence: 99%
“…Together with HIV-1 RT homology-based modeling and the functionality of chimeric P proteins carrying box E, or even the sequence encompassing the catalytic YMDD motif in box C to box E, from HIV-1 RT, these data demonstrate a common catalytic core architecture of the RT domains of hepadnaviral P proteins and retroviral RTs, in particular the formation of a primer grip-like structure by the box E residues in P proteins. Because the primer grip in HIV-1 RT is the target for multiple approved and experimental NNRTIs (13,18), the presence of a primer grip equivalent in P proteins suggests that related compounds might be developed into a new class of HBV inhibitors.…”
Section: Figmentioning
confidence: 99%